Validity, Sensitivity and Reliability of HAPUs E-book App for Preventing Incident of Pressure Ulcer on Patients - Ahmalia, Renty (Sahabat Publikasi Kuu, 2025)
Background: Pressure ulcers, or bedsores, are a global healthcare challenge, impacting patient well-being and placing significant economic burdens on healthcare systems. Despite advances in prevention strategies, hospital-acquired pressure injuries (HAPIs) remain prevalent due to aging populations, chronic conditions, and gaps in healthcare practices. Aims: This study evaluates the validity, reliability, sensitivity, and specificity of the HAPUs E-book app as a digital tool for educating nurses and preventing pressure ulcers. Methods: Using the Content Validity Index (CVI), eight experts (five wound care specialists and three IT experts) assessed the app's content validity. Sensitivity and specificity were calculated from trials involving 30 nurses, while Cronbach's Alpha Coefficient was used to evaluate internal consistency across key components. Results: The app achieved a CVI score of 1.00, indicating strong content validity. Sensitivity was 95.83%, and specificity was 83.33%, demonstrating high diagnostic accuracy. Cronbach's Alpha scores ranged from 0.73 to 0.82, confirming strong internal consistency and reliability. Conclusion: The HAPUs E-book app is a reliable tool for nursing education and pressure ulcer prevention. Its high sensitivity, specificity, and validated content make it suitable for clinical use and continuous professional development. However, further studies with larger populations are needed to generalize findings and assess long-term outcomes. Keywords: Pressure ulcers; Content Validity Index; CVI; mHealth; Validity